Prevalence of hypertension in Polish population of PURE Poland study - Szuba, Andrzej; Martynowicz, Helena; Zatońska, Katarzyna; Ilow, Rafał; Regulska-Ilow, Bożena; Różańska, Dorota; Wołyniec, Maria; Połtyn-Zaradna, Katarzyna; Zatoński, Witold (Journal of Health Inequalities, 2016)
Introduction Hypertension is the most common risk factor for cardiovascular disease and is a significant predictor of premature death and cardiovascular disability. The aim of this cohort study was to evaluate prevalence of hypertension and cardiovascular risk factors in studied population of Lower Silesia province in Poland. Material and methods : Presented results are a part of PURE project. The study group included 2,044 inhabitants Lower Silesia province. Data collection included clinical history, anthropometric data, blood pressure, and serum glucose. Prevalence, awareness, and treatment of hypertension were evaluated. Results : 60.3% of studied population were hypertensive. Hypertension was more prevalent in studied men (70.63%) than in women (57.24%). Education had a significant impact on prevalence of hypertension and the highest prevalence of hypertension was observed in the least educated group. Hypertension was undiagnosed in 48.5% of studied population. Significantly, more men than women had undiagnosed hypertension (53.4 vs. 44.3). The prevalence of undiagnosed hypertension significantly increased with the education level. Conclusions : The studied group had high prevalence of hypertension (60.3%). Hypertension was less frequent and better diagnosed in studied women than in men. Level of education had significant impact on prevalence and awareness of hypertension.